Hazard Identification, Risk Assessment and Control (HIRAC) On Physical, Health, and Psychosocial Aspects in the Cafeteria of University X Campus - Yosef Barita Sar Manik; Alya Syafiqa Z; Jauza Dzihni Alifa; Laura Angeline Hutahean; Melisa Aprina (Vokatek: Jurnal Pengabdian Masyarakat, 2026)
Campus canteens function as essential social and nutritional spaces within universities but often face overlooked Environmental, Health, and Safety (EHS) challenges. This study applies the Hazard Identification, Risk Assessment, and Control (HIRAC) framework in accordance with ISO 45001:2018 to evaluate occupational and environmental risks in the President University campus canteen. Hazard identification was conducted through direct observation, staff interviews, and document review, followed by a semi-quantitative risk assessment using a likelihood–severity matrix. Nineteen routine activities were analyzed and categorized into physical, health, and psychosocial hazards. The assessment identified cooking processes and reckless food consumption as the highest-risk activities (risk value = 12), primarily due to thermal exposure, smoke accumulation, and potential food contamination. Additional medium-risk hazards included unsafe packaging, poor food storage, and limited emergency access, while psychosocial risks such as stress and overcrowding were rated low to moderate. Overall, health-related hazards contributed most significantly to the canteen’s risk profile. The findings indicate that the limited application of HIRAC in canteen operations creates vulnerabilities in everyday food service activities. Strengthening canteen EHS performance requires assigning clear safety accountability, conducting routine risk monitoring, and implementing practical controls such as improved ventilation, allergen labeling, and personal protective equipment. Based on the proposed control measures, the estimated average risk value could potentially decrease from 12 to 4.8, indicating the possible effectiveness of integrating HIRAC into institutional safety management and fostering a more proactive safety culture in educational environments.